Gene Characterization - Thomas, Duncan C. (Statistical Methods in Genetic Epidemiology, 2004)
Suppose that we have identified a locus as a likely causal gene for the disease under study, a candidate gene. There are now a number of things we might wish to learn about that gene, including: whether in fact it is associated with the disease, after controlling for other risk factors such as ethnicity (see Chapter 9) the spectrum of mutations that occur among cases, as well as any neutral polymorphisms that occur no more commonly among cases than among the general population the biological effect of each mutation the genetic relative risks and dominance associated with each polymorphism the absolute age-specific penetrance function for each polymorphism the population allele frequencies for the different polymorphisms the molecular function of the gene